Mechanical Control of Myotendinous Junction Formation and Tendon Differentiation during Development - Valdivia, Mauricio; Vega-Macaya, Franco; Olguín, Patricio (Frontiers in Cell and Developmental Biology, 2017)
The development of the musculoskeletal system is a great model to study the interplay between inter-tissue chemical and mechanical signaling in cell adhesion, tissue morphogenesis and differentiation. In both vertebrates and invertebrates (e.g. Drosophila melanogaster) the formation of muscle-tendon interaction generates mechanical forces which are required for myotendinous junction maturation and tissue differentiation. In addition, these forces must be withstood by muscle and tendons in order to prevent detachment from each other, deformation or even lossing their integrity. Extracellular matrix remodeling at the myotendinous junction is key to resist mechanical load generated by muscle contraction. Recent evidences in vertebrates indicate that mechanical forces generated during junction formation regulate chemical signaling leading to extracellular matrix remodeling, however, the mechanotransduction mechanisms associated to this response remains elusive. In addition to extracellular matrix remodeling, the ability of Drosophila tendon-cells to bear mechanical load depends on rearrangement of tendon cell cytoskeleton, thus studying the molecular mechanisms involved in this process is critical to understand the contribution of mechanical forces to the development of the musculoskeletal system. Here, we will review recent findings regarding the role of chemical and mechanical signaling in myotendinous junction formation and tendon differentiation, and discuss molecular mechanisms of mechanotransduction that may allow Drosophila tendon cells to withstand mechanical load during development of the musculoskeletal system.